Managing the Perception of Coffee Shop Advertising Communications: A Neuromarketing Approach - Smykova М.; Yolсu С.; Sokhatskaya Н. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2025)
In the context of economic digitalization and increasing competition in the online environment, analyzing the effectiveness of advertising communications using neuromarketing tools becomes especially relevant. The aim of the article is to identify the gender-specific features of advertising perception based on eye-tracking analysis of promotional materials on social media. The study employed Eye Tracker equipment, which made it possible to record key metrics such as attention, visibility, and interest in various visual and textual elements of advertising messages. The results showed that the level of attention and interest was higher among men than women. The greatest engagement was observed in the advertisement for the opening of a new coffee shop, compared to the advertisement of the drink preparation process, indicating the presence of the "banner blindness" effect. It was also found that visual content attracts attention more quickly, while textual elements are viewed more consciously, highlighting the importance of their meaningful development. The scientific and practical significance of the research lies in the justification of approaches to the creation of advertising materials, taking into account gender specifics and features of visual perception, which can be used in the development of effective digital marketing strategies.